2022
DOI: 10.1001/jamasurg.2022.0809
|View full text |Cite
|
Sign up to set email alerts
|

Plating vs Closed Reduction for Fractures in the Distal Radius in Older Patients

Abstract: IMPORTANCE Distal radius fractures are common and are managed with or without surgery. Current evidence indicates surgical treatment is not superior to nonsurgical treatment at 12 months. OBJECTIVE Does surgical treatment for displaced distal radius fractures in patients 60 years or older provide better patient-reported wrist pain and function outcomes than nonsurgical treatment at 24 months? DESIGN, SETTING, AND PARTICIPANTS In this secondary analysis of a combined multicenter randomized clinical trial (RCT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…After the removal of duplicates, and screening of the titles, abstracts, and full texts, 112 articles were included in the systematic review ( Fig. 1 ) ( 6 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of duplicates, and screening of the titles, abstracts, and full texts, 112 articles were included in the systematic review ( Fig. 1 ) ( 6 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, and screening of the titles, abstracts, and full texts, 112 articles were included in the systematic review (Fig. 1) (6,10,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,…”
Section: Details Of the Included Studiesmentioning
confidence: 99%
“…Despite this, only 44.6% of the CR group perceived their treatment as "very successful," compared with 75% of the VLP group. The reasons remain unclear but may include preexisting perceptions with regard to the benefits of a surgical procedure 8 .…”
Section: Distal Radius and Wristmentioning
confidence: 99%
“…In clinical practice, closed reduction and immobilization with plaster or splint are the most common treatment methods for DRF [ 4 ]. Some studies have found no significant differences in the long-term prognosis between conservative and surgical treatment for DRF [ 5 , 6 ]. However, some studies have also shown that more than 25% of patients receiving conservative treatment may experience secondary reduction loss, and the incidence of fracture malunion or nonunion is higher.…”
Section: Introductionmentioning
confidence: 99%